Current challenges in performing PSM audits. Issue 2 (31st August 2021) - Hazzan, Michael J.; Rose, Martin R.; Heller, David M.; Sanderson, Scott
Abstract: In the last 2–3 years, Process Safety Management (PSM) audits have become more difficult to perform. As time has passed since the adoption of the PSM Standard and Risk Management Program (RMP) rule, as well as state PSM regulations, the guidance published in support of applying the regulations has expanded, while the regulations themselves, at least the federal ones, have remained static. Facilities have become more sensitive to the number and the nature of audit findings, continuous improvement in PSM programs has become somewhat controversial, and the definitions of "overdue" and "timely" have become more difficult to interpret and apply. These issues and others have conspired to create some of these difficulties.